A Data Driven Approach to Study the Social and Political Statuses of Urban Communities in Kunming. Issue 2 (July 2020) - Chang, Charles
Abstract: This article presents a data-driven approach to the study of the social and political statuses of urban communities in modern Kunming. Such information is lacking in government maps and documents. Using data from a wide variety of sources, many unconventional, I subject them to critical evaluation and computational analysis to extract information that can be used to produce a land use map of sufficient detail and accuracy to allow scholars to address and even answer questions of a socio-political, economic and, indeed, humanistic nature. My method can also be applied to other Chinese cities and to cities elsewhere that lack accurate information.